Produção textual: o que se ensina em turmas de 3º ano em escolas localizadas em territórios com alta vulnerabilidade? - Fonseca, Gleice Lima da [UNIFESP] (2016)
This study focuses on the teaching of writing textual production at the end of the year literacy cycle, third year of primary education in two schools in the city of São Paulo school, located in the same vulnerable territory. Broadly, it aims to understand how they are offered educational opportunities in Portuguese-speaking students who attend schools placed in locations with overlapping inequalities and fragile structures of opportunities in São Paulo. Integrates research in progress "competitive Interdependence and quality of educational opportunities" under the coordination of Professor. Dra. Claudia Lemos Vóvio and, in partnership with the NGO Cenpec. Specifically, it seeks to identify if and how the axis of content production of written texts is encompassed in literacy in both schools, and even if such proposals are consistent with the curriculum document officially adopted in this school system. It is noted that the poor results of school education in standardized ratings tend to get worse for residents of outlying areas and shortage of social goods, such as alert Kaztman (2001), Sant'Anna (2009) and Érnica and Batista (2012) by intervening in the teaching-learning process, leading to the deepening of social inequalities. it was decided to treat them as two case studies, observing four classes in one and three in the other. Therefore, told with access to the research database to which this study is integrated by examining the participant observation records of Portuguese classes, school notebooks, information about school performance and on socioeconomic and cultural contexts of the region. They were also generated new data from semi-structured interviews with coordinators of both schools. The results show that, first, there is great variation between what you expect children to learn in the shaft production of written texts and what is taught in two schools in literacy. The tasks aimed to the production of written texts are little requested during the school year in six of the seven groups. In most cases, a higher proportion of proposals that include other content, not intended for this stage of schooling. It was observed that the tasks are diverse and sustain themselves in different conceptions of language / language, evoking those in dispute in the educational and pedagogical field. However, the prevailing written request texts through tasks that secundarizam the function of the texts in society and aspects related to the conditions of production, circulation and communicative situation inherent in sociointeractionist theory and literacy, as contained in the curriculum document. The relevance of this research lies in the possibility of understanding what is taught in Portuguese, in schools located in areas with social vulnerabilities and thus produce indications for teacher training in relation to the proposed production of written texts in literacy, favoring formation of autonomous users written form of the language and the fair distribution of goods relating to the schooling process.